Meyppattiyal dalam novel-novel Sujatha - P.Devaki M.K. Perumal (2021)
This research aims to identify meyppattiyal (emotions), explain inner causes (variousemotions) that trigger meyppattiyal, analyse thunaimai meyppattiyal (additionalemotions) and explain messages conveyed by Sujatha in his novels by incorporating meyppattiyal. This study analyses five of Sujathas novels consisting Vasanth! Vasanth!, Miindum OruKuttram, Priya, Aayarathil Iruvar and Pesum Bommaikal This is a qualitative research thatcombines library research and text analysis methods. Analysis and discussions are based onmeyppattiyal theory prompted by Tolkappiyar which includes envakai meyppattiyal (eight-fold emotions) consisting of nakai (laughter), alukai (weeping), ilivaral (contempt),marutkai (awe), accam (fear), perumitam (pride), vekuli (anger) and uvakai (joy) depicted inSujathas novels. Each of the meyppattiyal is triggered by four inner causes and which thereforeproduce other 32 other causes. Besides 32 main meyppattiyal, there are also another 32 additionalmeyppattiyal. This research was done based on 64 meyppattiyal. The findings show that author hadsuccessfully invoked 27 out of the 32 main meyppattiyal and 25 of the 32 additional meyppattiyalin five novels. 13 values are also implicitly incorporated in these novels. In conclusion,this study reveals characters and settings in Sujatha's novels are closely related to meyppattiyalas mentioned in Tolkappiyam. The implication is, this study encourages individuals to manage theiremotions effectively and assimilatepositive feelings towards a harmonious society.